Global transcriptome analysis of the C57BL/6J mouse testis by SAGE: evidence for nonrandom gene order - Divina, Petr; Vlcek, Cestmír; Strnad, Petr; Paces, Václav; Forejt, Jirí (BMC genomics, 2005)
BACKGROUND: We generated the gene expression profile of the total testis from the adult C57BL/6J male mice using serial analysis of gene expression (SAGE). Two high-quality SAGE libraries containing a total of 76 854 tags were constructed. An extensive bioinformatic analysis and comparison of SAGE transcriptomes of the total testis, testicular somatic cells and other mouse tissues was performed and the theory of male-biased gene accumulation on the X chromosome was tested. RESULTS: We sorted out 829 genes predominantly expressed from the germinal part and 944 genes from the somatic part of the testis. The genes preferentially and specifically expressed in total testis and testicular somatic cells were identified by comparing the testis SAGE transcriptomes to the available transcriptomes of seven non-testis tissues. We uncovered chromosomal clusters of adjacent genes with preferential expression in total testis and testicular somatic cells by a genome-wide search and found that the clusters encompassed a significantly higher number of genes than expected by chance. We observed a significant 3.2-fold enrichment of the proportion of X-linked genes specific for testicular somatic cells, while the proportions of X-linked genes specific for total testis and for other tissues were comparable. In contrast to the tissue-specific genes, an under-representation of X-linked genes in the total testis transcriptome but not in the transcriptomes of testicular somatic cells and other tissues was detected. CONCLUSION: Our results provide new evidence in favor of the theory of male-biased genes accumulation on the X chromosome in testicular somatic cells and indicate the opposite action of the meiotic X-inactivation in testicular germ cells.
Keywords: Gene Expression Regulation; Multigene Family; Gene Library; Male; Cluster Analysis; genová knihovna; Models, Statistical; výpočetní biologie; Sequence Analysis, DNA; Transcription, Genetic; sekvenční analýza DNA; shluková analýza; Databases, Genetic; mužské pohlaví; statistické modely; chromozom X; Data Interpretation, Statistical; stanovení celkové genové exprese; Genomics; Testis; Gene Order; Genetic Linkage; Gene Expression Profiling; genetická transkripce; X Chromosome; databáze genetické; Animals; RNA; genetická vazba; zvířata; regulace genové exprese; testis; myši inbrední C57BL; interpretace statistických dat; myši; Mice, Inbred C57BL; multigenová rodina; Mice; Computational Biology; pořadí genů; genomika